Liberating and Oppressive Factors for Self-Directed Learning: A Systematic Literature Review - Asta Vaičiūnienė; Aušra Kazlauskienė (Education Sciences, 2023)
Self-directed learning (SDL) is one of the key competencies that provides the conditions necessary for adjustments to changes in the social context, and it should be developed from the early years of schooling. The effect of SDL on learners’ motivation and attainments has been proven, and its value in enabling learners to change has been substantiated. When applying it in practice, difficulties are faced because SDL-based pedagogy sets challenges for both school students and teachers. It is important to carry out a systematic analysis investigating factors that provide the conditions for the self-directed learning of students. A systematic analysis (applying methods of systematic reviews and meta-analysis (PRISMA)) allows us to emphasize that the liberating factors of SDL include learning environments (support/scaffolding, teaching and learning strategies, physical environment and technological resources, autonomy, assessment and self-assessment, feedback, sustainable and positive climate), obtained knowledge, abilities (self-efficacy, cognitive competence, time management, meta-learning skills), and the learner’s proactivity (collaboration, meeting learners’ needs, possibilities, search for learning support, and raising questions). The oppressive factors of SDL when dealing with learning environments for both learners and teachers (learning load, teaching and learning strategies, teacher power, anxiety, negative emotions, assessment, absence of feedback, control, lack of learning support) as well as educational institutions (teacher support, learning facilities, culture of encouragement and support) are discussed.